The Aesthetics of Rhyme in Modern Arabic Poetry - belabaci, mehamed (El Omda in Linguistics and Discourse Analysis, 2018)
The “Hooves of Poetry” have accompanied poetry throughout all its rhetorical and communicative paths over its long journey. Indeed, they may be the poet’s greatest preoccupation in capturing them to craft their poetic canvases, given their enchantment in silent-yet-resonant or resonant-yet-silent pauses. These are sonic bundles composed of vowels and consonantal rests that cascade over the ends of the poetic lines in their ornamental and musical vessels, or they take the form of measured, counted, and bound rhythms and movements at the ends of verses or lines.